COMPARISON OF SOLID VERSUS CANNULATED INTERLOCK INTRAMEDULLARY NAILS FOR MANAGEMENT OF ISOLATED FEMORAL SHAFT FRACTURES - M.Abdul Rehman Yaseen; Mazhar Mehmood; Muhammad Javaid Iqbal (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: Compare the frequency of post-operative surgical site infection of solid interlock intramedullary nail with cannulated open interlock intramedullary nail for management of isolated femoral fracture. METHODOLOGY: A total of 100 cases (50 in each group) with Isolated femoral shaft fracture, Closed femoral shaft fractures or Gustilo and Anderson classiﬁcation type I open femoral shaft fractures, Solid and cannulated open interlock ﬁxation for femur shaft fractures between 20-60 years of age of either gender were enrolled in the study. Patients with bilateral femur fractures, Ipsilateral fracture of any other bone of involved side, unﬁt for surgery or anesthesia with comorbid condition, conversion to intramedullary nailing from external ﬁxator of femur and presented after 30 days of fracture were excluded from the study. RESULTS: In our study, out of 100 cases, (50 in each group), 18%(n=9) in Group-A and 16%(n=8) in Group-B were between 20-40 years of age while 82%(n=41) in Group-A and 84%(n=42) in Group-B were between 41-60 years of age, mean+sd was calculated as 46.78+7.53 years in Group-A and 47.76+6.49 years in Group-B, 62%(n=31) in Group-A and 60%(n=30) in Group-B were male while remaining 38%(n=19) in Group-A and 40%(n=20) in Group-B were females, surgical site infection was compared in both groups and it was recorded in 26%(n=13) in Group-A and 56%(n=28) in Group-B while remaining 74%(n=37) in Group-A and 44%(n=22) in Group-B had no ﬁndings of the morbidity, p value was calculated as 0.00 showing a signiﬁcant diﬀerence between the two groups. CONCLUSION: We concluded that the frequency of post-operative surgical site infection of solid interlock intramedullary nail is signiﬁcantly lower when compared with cannulated open interlock intramedullary nail for management of isolated femoral fracture. However, our results may create awareness regarding use of solid interlock intramedullary nail for the management of femoral shaft fracture.